Gastrointestinal symptoms and elevated levels of anti- saccharomyces cerevisiae antibodies are associated with higher disease activity in Colombian patients with spondyloarthritis (2017)
Background. Spondyloarthritis (SpA) is a group of articular inflammatory rheumatic diseases that their gastrointestinal manifestations are around 10% of their extra-articular symptoms, supporting that the inflammatory response of the intestinal mucosa could be associated with the clinical status. Objectives. To investigate the association between gastrointestinal symptoms and autoantibodies and disease activity between SpA patients, healthy subjects (HS), and patients with inflammatory bowel disease (IBD). Methods. 102 SpA patients, 29 IBD patients, and 117 HS were included. Autoantibodies as ASCA, ANCA, anti-tTG, anti-DGP, ANA, and IgA were measured. The patients were assessed to evaluate clinical and gastrointestinal symptoms. An association analysis was performed using Chi square test and a logistic regression. Results. Significant ifferences were found for ASCA levels in SpA (28.2%) compared to IBD (14.2%) and HS (6.0%) (p = 0.029), as well as for ANAS in SpA (49.5%) and IBD (37.9%) (p < 0.001) and abdominal pain (p = 0.012) between SpA (54.3%) and IBD (27.5%). Significant associations were found between ASDAI > 4 and gastrointestinal symptoms (p < 0.05) and IgA (p = 0.007). The association for abdominal bloating was maintained (OR: 3.93, CI-95%, 1.14–13.56; p = 0.030). Conclusions. Gastrointestinal symptoms, ASCA, ANAS, and IgA levels were associated with high disease activity in SpA compared with IBD and HS.